Determinan Variabel Return of Assets (ROA), Dana Pihak Ketiga (DPK) dan Inflasi Terhadap Pembiayaan BPRS di Indonesia - Andi Nur Azizah Fajry Azzahrah (Program Studi Ekonomi Syariah, 2018)
This research is aims to determine the effects of retun of assets, depositor fund, and macroeconomic varable toward financing in shariah rural bank in Indonesia perode January 2013 – December 2016. Variables used in the research are return of assets, depositor fund and inflation. The data in this research is quantitative data which is a secondary data in monthly data obtained from the websute of Bank Indonesia and Otoritas Jasa Keuangan.nData were tested time series. The population was shariah rural bank in Indonesia. The methods of data analysis was using Error Correction Model. The results showed that on long term ROA has negative effects and significant on financing, while variable DPK has positive effects and significant on financing and variable inflation has no effects on financing. On short term ROA has no effects on financing, while variable DPK has negative effects and significant on financing and inflation has no effects on financing.